RISK MANAGEMENT IN ISLAMIC BANKS: A RESEARCH ON THE PARTICIPATION BANKS IN TURKEY - Hüseyin Çetin; Raif Parlakkaya; Mustafa Nihat Demirci (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Risk management is of strategic importance for banks whose operations are largely based on risky transactions. Islamic banks face almost all risks exposed in conventional banks. Risks are further diversified and complicated in Islamic banks. In this respect, risk management in these banks requires some unique risk measurement, risk mitigation and risk management systems. Also, Islamic banks cannot use some of the methods used by conventional banks in risk management. Therefore, there is a need for unique methods compliant with Shariah principles. In this paper, a detailed literature review has been conducted on studies investigating risk management in Islamic banks and the theoretical framework of the subject was established. Then, a qualitative research was conducted in order to identify the main risks encountered in Islamic (Participation) banks operating in Turkey. The risk management techniques of these banks were examined and compared with conventional banks. Also, main problems in risk management were determined and possible solutions were recommended in this context. Within the scope of the research, the data obtained by the interview method was interpreted by descriptive analysis method. According to results, risk management in Islamic banks is largely similar to conventional banks. On the other hand, different types of risks encountered in these banks and the obligation to comply with Islamic principles differentiate Islamic banks in the risk management process.